Design, prototyping, and acoustic testing of protective cases for AudioMoth recorders using digital fabrication technologies - Tabash-Pérez , Farith (2026)
Acoustic monitoring of the environment has increased in recent years and is considered a minimally invasive technique for study wildlife. This increase has favored the development of new technologies, for example, the AudioMoth board. This small electronic board records sounds from nature, but under adverse environmental conditions, it can be easily damaged; although protectors have been developed, access to them is limited. Currently, alternative shields with different designs have been implemented, but their functionality has not been evaluated through acoustic testing. Three prototypes made using digital fabrication technologies were evaluated based on suggestions from users who are experts in bioacoustics. Their performance was tested in a controlled environment, a humid ecosystem and a dry ecosystem by comparing traditional acoustic indices. The results show that the best performance was obtained by the resin-based protector prototype, since, given the characteristics of the material, it provides the greatest protection and modifies the acoustic variables to a lesser degree when compared to the protection by means of a plastic bag that has been used as a traditional method. Based on the results, design recommendations were provided for the selected prototype. The design and evaluation of these protectors can prevent future damage to the plate and maintain its functionality, despite the conditions of tropical ecosystems.